2023
DOI: 10.3390/diseases11020072
|View full text |Cite
|
Sign up to set email alerts
|

Towards Understanding the Key Signature Pathways Associated from Differentially Expressed Gene Analysis in an Indian Prostate Cancer Cohort

Abstract: Prostate cancer (PCa) is one of the most prevalent cancers among men in India. Although studies on PCa have dealt with genetics, genomics, and the environmental influence in the causality of PCa, not many studies employing the Next Generation Sequencing (NGS) approaches of PCa have been carried out. In our previous study, we identified some causal genes and mutations specific to Indian PCa using Whole Exome Sequencing (WES). In the recent past, with the help of different cancer consortiums such as The Cancer G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 96 publications
0
3
0
Order By: Relevance
“…From our recently published RNA-Seq analyses ( Shukla et al 2023), 11 lncRNAs identified (SCARNA10, LINC01973, LINC00940, NPBWR1, FLJ16779, ANKRD20A9P, LINC00298, SNHG19, LOC341056, TLX1NB, LINC00662:60) were screened in the form of FASTA files which were then retrieved as discussed previously (using NCBI, NONCODE, LINCipedia and RNA central public portals). We considered the HDOCK web server for the molecular docking studies to identify the interactions of receptor-ligands.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From our recently published RNA-Seq analyses ( Shukla et al 2023), 11 lncRNAs identified (SCARNA10, LINC01973, LINC00940, NPBWR1, FLJ16779, ANKRD20A9P, LINC00298, SNHG19, LOC341056, TLX1NB, LINC00662:60) were screened in the form of FASTA files which were then retrieved as discussed previously (using NCBI, NONCODE, LINCipedia and RNA central public portals). We considered the HDOCK web server for the molecular docking studies to identify the interactions of receptor-ligands.…”
Section: Resultsmentioning
confidence: 99%
“…Few limitations such as rearrangement were not considered in aneuploidy. In our lab, RNA-seq data from a small cohort of PCa patients was analyzed and some critical lncRNAs were identified as deterministic markers (Shukla et al, 2023). In present study, docking analysis of prostate specific proteins and AR with lncRNAs was performed to explore binding potential towards identifying interacting residues and putative RNA-binding motifs.…”
Section: Lncrna-pca Interactionsmentioning
confidence: 99%
See 1 more Smart Citation